تسوية النزاعات الدوليه بالطرق الودية دراسة مقارنة بين الفقه الإسلامي والقانون الدولي - دركي, ليلي; معمير, شيماء (جامعة الوادي university of eloued, 2023)
لقدعالجت الدراسة تسوية النزاعات الدولية بالطرق الوديةبيْن الفقه الإسلامي والقانون الدولي، وذلك من خلال ثلاث مباحثِ: فقد خصصنا أولهما تحديد مصطلحات تسوية النزاعات الدولية في الفقه الإسلامي والقانون الدولي، وخصص ثانيهما بتحديد الآليات الودية في تسوية النزاعات الدولية في الفقه الإسلامي والقانون الدولي أما المبحث الثالث عرضنا فيه تطبيقات تسوية النزاعات الدولية بالطرق الودية في الفقه الإسلامي والقانون الدولي، ومِنَ النتائجِ الأساسيةِ التي وصلَ إليها البحثُ في هذا الموضوعِ أن تسوية النزاعات الدولية بالطرق الودية، هو مبدأ من المبادئ الأساسية التي يسعي إليها كلٌ من الفقه الإسلامي والقانون الدولي وذلك لتجنب الوقوع في النزاعات مسلحة والحفاظ على الأمن والسلم الدوليين، ونقترح في هذا المجال العمل على تطوير وتنمية المنظمات الدولية وتنقيح مواثيقها واستحداث أساليب جديدة حتى تواكب الساحة الدولية.he study dealt with the amicable settlement ofinternational disputes between Islamic jurisprudence and international law through three titles: first, the definition of terms for the settlement of international disputes chapters in Islamic jurisprudence and international law. The second was devoted to the identification of friendly mechanisms in the settlement of international disputes in Islamic jurisprudence and international law. The third about the study that had presented the applications of the friendly settlement of international disputes in Islamic jurisprudence and international law. And one of the fundamental findings of the research on this topic is that the settlement of international disputes by amicable means, It is one of the fundamental principles pursued by both Islamic jurisprudence and international law to avoid being caught in armed conflicts and to maintain international peace and security development and development of international organizations, revision of their charters and development of new methods to keep pace with the international arena.
حديث
Keywords: الطرق - النزاعات - تسوية - الودية; Routes -Disputes-Settlement-Cordiality